Margins of Error: Performance, Text, and the Editing of Early Modern Sermons. (18th December 2020) - Rhatigan, Emma
Abstract: This article explores the editing of early-modern sermons, with a particular focus on the challenge of recovering the sermon in performance. Taking as its starting point the fact that most sermons were not written out until after their delivery in the pulpit, it considers the ways in which sermons resist conventional editorial methods based on the identification of 'error' and the reconstruction of a holograph text. It argues for a new approach to editing and a new perspective on error which uses these moments of textual complexity in order to shed light on a sermons evolution from sermon notes and pulpit delivery to written text.